Effective strategies for teaching philological disciplines: practicalc ases and Innovative approaches - Inna Varvaruk; Inna Sakhnevych; Nataliia Hasiuk; Tetiana Muzika; Oleksandr Lada (Universidade Estadual de Alagoas, 2024)
This article delves into the expediency of exploring effective strategies for teaching philological disciplines, emphasizing the critical importance of innovative approaches in modern educational practices. As the field of philology continues to evolve, the relevance of enhancing teaching methodologies to meet the diverse learning needs of students becomes increasingly evident. The primary objective of this study is to investigate practical cases and innovative approaches that can significantly impact the pedagogical landscape of philological education. Utilizing a qualitative research approach, the article examines the efficacy of implementing various teaching strategies in philological disciplines and their implications for student engagement and academic performance. Through case studies and theoretical analysis, the research reveals the effectiveness of interactive teaching methods, collaborative learning activities, and technology integration in philological education. The results highlight the potential for these innovative approaches to enhance student comprehension, critical thinking skills, and overall academic achievement, ultimately contributing to the advancement of teaching practices in philological disciplines. The practical and theoretical significance of these findings lies in the increased efficiency and effectiveness of teaching methods, leading to improved learning outcomes and student success in the field of philology.